2017
DOI: 10.1523/jneurosci.0168-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disrupts High-Level Speech Parsing Despite Significant Basic Auditory Processing

Abstract: The extent to which the sleeping brain processes sensory information remains unclear. This is particularly true for continuous and complex stimuli such as speech, in which information is organized into hierarchically embedded structures. Recently, novel metrics for assessing the neural representation of continuous speech have been developed using noninvasive brain recordings that have thus far only been tested during wakefulness. Here we investigated, for the first time, the sleeping brain's capacity to proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 62 publications
(40 reference statements)
7
93
2
Order By: Relevance
“…TMR has been shown to influence hippocampal activity during sleep (Rasch et al, 2007;Rothschild et al, 2017), suggesting that sounds can modulate activity in association cortices. On the other hand, non-invasive imaging in humans suggests that during sleep, auditory responses downstream from auditory cortex (AC) are attenuated: studies using magnetoencephalography (MEG) (Kakigi et al, 2003;Strauss et al, 2015), electroencephalography (EEG) (Makov et al, 2017), and functional magnetic resonance imaging (fMRI) (Portas et al, 2000) suggest comparable responses across vigilance states in early sensory regions and robust attenuation in association cortex. However, investigation of sensory responses downstream from sensory cortical regions at the level of neuronal spiking activity is still missing.…”
Section: Do Sounds Effectively Modulate Responses In Downstream Assocmentioning
confidence: 99%
“…TMR has been shown to influence hippocampal activity during sleep (Rasch et al, 2007;Rothschild et al, 2017), suggesting that sounds can modulate activity in association cortices. On the other hand, non-invasive imaging in humans suggests that during sleep, auditory responses downstream from auditory cortex (AC) are attenuated: studies using magnetoencephalography (MEG) (Kakigi et al, 2003;Strauss et al, 2015), electroencephalography (EEG) (Makov et al, 2017), and functional magnetic resonance imaging (fMRI) (Portas et al, 2000) suggest comparable responses across vigilance states in early sensory regions and robust attenuation in association cortex. However, investigation of sensory responses downstream from sensory cortical regions at the level of neuronal spiking activity is still missing.…”
Section: Do Sounds Effectively Modulate Responses In Downstream Assocmentioning
confidence: 99%
“…properties and PAC responses(50) vs. high-order activity in association cortex (51). Thus, a functional disconnection between primary sensory and association cortex may be a general property of LOC not only due to anesthesia, as demonstrated also by direct perturbation of cortical activity with transcranial magnetic stimulation (TMS) (52)(53)(54).…”
Section: Studies In Natural Sleep Demonstrate a Similar Distinction Bmentioning
confidence: 99%
“…Neural tracking of linguistic structures strongly depends on the task, demonstrating an active chunking process. Neural tracking of multisyllabic words and multi-word chunks is largely abolished during sleep (Makov et al, 2017) or when the listeners are distracted by competing sensory stimuli . Here, it is further demonstrated that neural tracking of a structurally ambiguous sequence relies on the chunking rule.…”
Section: Rule-based Chunking Hypothesismentioning
confidence: 99%
“…Recent neurophysiological results have been shown that when presented with speech, the brain concurrently tracks multiple levels of linguistic units, such as sentences, phrases, words, and syllables ( Fig. 1) (Ding et al, 2016;Makov et al, 2017;Brodbeck et al, 2018;Broderick et al, 2018;Ding et al, 2018;Keitel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%